Stereotyping and Othering of Non-White Characters in “Harry Potter” Movies - Nadia Adelia (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
This thesis focuses on the way the non-white characters, such as Black and Asian, are portrayed in Harry Potter movies. The non-white people are put in the group of unimportant characters. Their characters seem to be portrayed differently compared to the white characters in term of their characterizations. Using film language theory, such as body language and dialogue, I find there are Stereotyping and Othering towards the non-white characters. I analyze the Stereotyping toward non-white characters such as Cho Chang and Kingsley Shacklebolt as the Asian and Black character using the gestures, facial expression, costumes, and dialogues. I also analyze the Othering towards non-white characters such as Centaurs and Dre Head as the non-human characters using the appearance, accents, and costume. Also, the Yule Ball costume for Cho Chang and Patil twins also shows exoticism because of the races of the characters. Keywords: Racism, Stereotyping, Othering, Representation, Fantasy Fiction